Multi-material model for the simulation of powder bed fusion additive manufacturing - Küng, Vera; Scherr, Robert; Markl, Matthias; Körner, Carolin (Computational Materials Science, 2021)
Powder bed fusion (PBF) is an additive manufacturing process that allows for the production of individual metal parts with high geometric freedom. An additional degree of freedom can be introduced by multi-material fabrication, i.e. the processing of a powder mixture from different materials. This can be used to perform in situ alloying or to produce functionally graded parts. The thereby increased complexity intensifies the need to simulate the PBF process in order to replace costly and time-consuming experiments. In this paper, a multi-material model for the lattice Boltzmann-based simulation of the mixing of two elements to a binary alloy via PBF is presented. Its foundation is a consistent thermodynamic model comprised of the mass, momentum and enthalpy conservation equations, including element-specific mass conservation and the often neglected physical effect of enthalpy diffusion. Based on this, the material model considers concentration-dependent material parameters such as heat capacities and latent heats. In particular, melting and solidification are modelled in accordance with the phase diagram, for which the example of an isomorphous one is given. The comparison of simulation results with analytical calculations shows excellent agreement for different scenarios, in which the transport phenomena of diffusion and heat conduction are verified. Regarding the PBF process, the simulation of a single melt track in a multi-material powder mixture predicts the partitioning of the melt pool into an inner well-mixed region surrounded by melt of the lower-melting component. A multi-track and multi-layer simulation, which illustrates the build-up of a compact sample, shows that unmolten particles as well as a very high surface roughness are possible unwanted side effects in multi-material PBF.
Keywords: Additive manufacturing; Multi-material; Multi-component; In situ alloying; Mesoscopic simulation